Corporate distinctive competence, strategy, industry and performance - Hitt, Michael A.; Ireland, R. Duane (Strategic Management Journal, 1985)
Abstract Corporate distinctive competencies may facilitate effective management of interdependencies among multiple units. Relationships between corporate distinctive competencies and firm performance were examined in 185 industrial firms. Results suggested that distinctive competencies associated with performance vary according to the grand strategy used and the firm's principal industry. Specific distinctive competencies were identified for each strategy and industry type.